Analisis Kinerja Pelayanan Administrasi pada Sekretariat DPRD Kabupaten Deli Serdang dalam Mendukung Efektivitas Tugas dan Fungsi Legislatif - Fadilaturrahmah; Apen Olita; Fanzi Akhmarozi; Nazwa Indah Lestari; Nurfadilah; Emelia Rahmadany Putri Gami (LPPM Politeknik Piksi Ganesha, 2026)
This research aims to analyze in depth how the performance of administrative services carried out by the Secretariat of the Deli Serdang Regency DPRD in supporting the effectiveness of the implementation of legislative tasks and functions, as well as identifying various obstacles faced in the service process. The research method used is a qualitative descriptive approach with data collection techniques through direct observation, in-depth interviews with employees, and documentation during the implementation of Internship Lectures (KKM) activities. The research results show that in general the administrative services have run quite well and are able to support the operational activities of the DPRD, but there are still some problems such as limited competent human resources, lack of optimal utilization of information technology in the administrative system, and lack of maximum coordination between work departments. Therefore, improvement efforts are needed through improving the quality of human resources, the development of a digital-based administrative system, and strengthening internal coordination to improve the quality of service sustainably.